Industrial enzyme production in Bangladesh: current landscape, scope, and challenges (Asian Journal of Medical and Biological Research, 2023)
Enzymes are important biological catalysts that perform specialized functions within living organisms. Industrial enzymes are crucial in various sectors, including pharmaceuticals, the textile industry, the manufacturing of chemicals, biodiesel, the food and beverages industry, and consumer goods. Enzymes can be obtained from multiple sources, including microbes, animals, and plants.  Microorganisms, especially bacteria and fungi, provide more than 50% of industrial enzymes because of their advantageous growth features, low nutritional needs, and biochemical diversity.  Bangladesh's economy relies heavily on agriculture and generates biomass energy from waste such as rice husk, straw, jute sticks, and sugarcane bagasse. To reduce the environmental impact, it is vital to modify these waste materials into beneficial industrial and commercial products, like enzymes. This review article investigates the current landscape, scope, and challenges of industrial enzyme production in Bangladesh. Bangladesh has become an appealing destination for biotech firms due to variables such as yearly bio-product imports, local market consumer demand, and the availability of resources and competent people. In 2021, Bangladesh ranked as the 34th largest importer of enzymes worldwide, with an import value of $47.4 million. Bangladesh mainly imports enzymes from Turkey, Malaysia, China, Singapore, and Sri Lanka. This study identifies a critical research gap, which is the lack of a dedicated industrial enzyme production industry in Bangladesh. This gap is impeding large-scale implementation, despite ongoing research efforts. Furthermore, we suggest the establishment of a specialized industrial enzyme production sector in Bangladesh, which would benefit the environment and promote economic growth through the utilization of agro-industrial waste resources. Finally, this thorough assessment of current industrial enzyme research in Bangladesh seeks to provide researchers and stakeholders with essential information for future development. Collaboration between the government, businesses, and academics is critical to fostering growth and capitalizing on the potential of the worldwide enzyme industry.Asian J. Med. Biol. Res. 2023, 9 (4), 145-159